Perceived impact of conditional cash transfer programs on education, health, and nutrition in South Cotabato, Philippines - Jun Rex H. Halique; Prescillano D. Campado (International Review of Social Sciences Research)
The conditional cash transfer program, a crucial initiative aimed at breaking the intergenerational cycle of poverty in the Philippines, invests in the education, health, and nutrition of the financially challenged sector of society. This study assesses the impact of the program's implementation on education, health, and nutrition and the challenges the policy implementers and beneficiaries face during its execution. The program's implementation was evaluated through a survey among the beneficiaries and policy implementers, and the problems encountered were examined through a focus group discussion. A triangulation method was employed to comprehensively understand the agreement of results from policy implementers, beneficiaries, and government reports. This paper asserts that the Philippine government's conditional cash transfer program positively impacts the education and health programs, thereby protecting the next generation of human capital. However, it also highlights the need to assess the program's impact on nutrition further. There is no direct evidence that the program effectively addresses stunting. There is also no relationship between the program implementation and the problems encountered. The primary issue beneficiaries face is the timely release of cash grants. This study offers valuable insights on how the national government can improve the program design and implementation especially the release of cash grants. While this study affirms the program’s effectiveness, there is a need to study the status of the students who have graduated from the program.